The Legal Complexities of Wali Hakim in Islamic Marriages: Comparative Insights from Indonesia and Beyond - Ade, Faisal; Menad, Safia (Antmind Review: Journal of Sharia and Legal Ethics, 2025)
This study explores the legal complexities surrounding Islamic marriages, focusing specifically on the critical role of Wali Hakim in circumstances where Wali Nasab is unavailable or deemed 'adhal' (recalcitrant). In Islamic jurisprudence, the Wali Hakim acts as a legal guardian appointed to perform marriage ceremonies in cases where the traditional Wali Nasab is either absent, incapacitated, or refuses to perform the marital contract. This research utilizes a mixed-methods approach, including qualitative interviews with religious and community leaders, analysis of existing legal frameworks, and comparative studies of international practices. The findings reveal significant variations in the application and understanding of Wali Hakim across different jurisdictions, highlighting both the challenges and legal interpretations faced within Indonesia. Comparative insights are drawn from other Islamic countries and international legal standards to provide a broader context. The study identifies key discrepancies and recommends potential reforms to align Indonesian practices with international norms. The implications of these findings underscore the need for a nuanced approach to the application of Wali Hakim, balancing traditional Islamic principles with contemporary legal practices. This work contributes to the ongoing discourse on the evolution of Islamic family law and its intersection with modern legal systems.